STRENGTHENING COMMUNITY RESILIENCE FROM THE EFFECT OF DRUGS IN UBUD TOURISM VILLAGE - I Nyoman Gede Sugiartha (Awang Long Law Review, 2021)
As a higher education institution, Warmadewa University must ensure that it always obeys the Tridharma of Higher Education following the predetermined vision and mission. Now every lecturer is encouraged to be able to package community service activities both in groups and individuals which will later show concern for the community. Community service activities can be carried out by providing enlightenment by providing legal counseling and consultation to the community in various fields of life in the field of environment and tourism. One thing that should be observed is the influence of narcotics in tourist areas in Ubud Village where it is hoped that every member of the community, Banjar Adat is required to have a plan on improving the community from the impact of tourism. This is stated in the formulation of the problem; 1) The dangers of drugs for the community in the development of tourism in Ubud Village 2) The synergy of the community with the National Narcotics Agency with the Police in preventing drug crimes. This service is expected to explain; the dangers of narcotics for community development, and the function of the National Narcotics Agency and the Police in drug crimes in Indonesia. For the community, this service can be used as reference material to learn and find out new things in the legal field, especially criminal law related to drug crimes. Efforts should be pursued and do not hesitate to carry out daily orders against tourists who come to Ubud, this impression is certainly expected for tourists who visit not to be free to bring drugs that are prohibited by the government. Of course, the final result can strengthen the resilience of the community in Ubud Village against the influence of drugs that can damage the resilience both physically and mentally of the community.